PENGARUH FRAUD PENTAGON PADA KECURANGAN LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR - Cahyanita, Bintang Nadya; Palupi, Agustin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to investigate the impact of the Pentagon fraud case on fraudulent practices in manufacturing company financial reports. The Pentagon fraud case is one of the cases involving manipulation of financial reports. This research uses a sample of companies in the consumer cyclicals and consumer non-cyclicals sectors which are successively listed on the Indonesia Stock Exchange (BEI) in 2020-2022. This research sample used a purposive sampling method with a research sample of 176 companies. The research method for measuring the existence of manufacturing company financial reports uses the F-Score model. The results of this research show that financial targets and the nature of the industry have an influence on the condition of financial statements. Meanwhile, external pressure, financial stability, change of auditor, proportion of independent board of commissioners, and number of CEO photos have no influence on the condition of the financial statements.